Discrepancy Between European Association of Urology Guidelines and Daily Practice in the Management of Non-muscle-invasive Bladder Cancer: Results of a European Survey - Hendricksen, Kees; Aziz, Atiqullah; Bes, Perrine; Chun, Felix K-H; Dobruch, Jakub; Kluth, Luis A; Gontero, Paolo; Necchi, Andrea; Noon, Aidan P; van Rhijn, Bas W G; Rink, Michael; Roghmann, Florian; et al. (European urology focus, 2019)
BACKGROUND: The European Association of Urology (EAU) non-muscle-invasive bladder cancer (NMIBC) guidelines are meant to help minimise morbidity and improve the care of patients with NMIBC. However, there may be underuse of guideline-recommended care in this potentially curable cohort. OBJECTIVE: To assess European physicians' current practice in the management of NMIBC and evaluate its concordance with the EAU 2013 guidelines. DESIGN, SETTING, AND PARTICIPANTS: Initial 45-min telephone interviews were conducted with 20 urologists to develop a 26-item questionnaire for a 30-min online quantitative interview. A total of 498 physicians with predefined experience in treatment of NMIBC patients, from nine European countries, completed the online interviews. OUTCOME MEASUREMENTS AND STATISTICAL ANALYSIS: Descriptive statistics of absolute numbers and percentages of the use of diagnostic tools, risk group stratification, treatment options chosen, and follow-up regimens were used. RESULTS AND LIMITATIONS: Guidelines are used by ≥87% of physicians, with the EAU guidelines being the most used ones (71-100%). Cystoscopy (60-97%) and ultrasonography (42-95%) are the most used diagnostic techniques. Using EAU risk classification, 40-69% and 88-100% of physicians correctly identify all the prognostic factors for low- and high-risk tumours, respectively. Re-transurethral resection of the bladder tumour (re-TURB) is performed in 25-75% of low-risk and 55-98% of high-risk patients. Between 21% and 88% of patients received a single instillation of chemotherapy within 24h after TURB. Adjuvant intravesical treatment is not given to 6-62%, 2-33%, and 1-20% of the patients with low-, intermediate-, and high-risk NMIBC, respectively. Patients with low-risk NMIBC are likely to be overmonitored and those with high-risk NMIBC undermonitored. Our study is limited by the possible recall bias of the selected physicians. CONCLUSIONS: Although most European physicians claim to apply the EAU guidelines, adherence to them is low in daily practice. PATIENT SUMMARY: Our survey among European physicians investigated discrepancies between guidelines and daily practice in the management of non-muscle-invasive bladder cancer (NMIBC). We conclude that the use of the recommended diagnostic tools, risk-stratification of NMIBC, and performance of re-TURB have been adopted, but adjuvant intravesical treatment and follow-up are not uniformly applied.
Keywords: nádory močového měchýře; Health Care Surveys; lékařská praxe - způsoby provádění; Evropa; Europe; Neoplasm Invasiveness; Practice Patterns, Physicians'; Urinary Bladder Neoplasms; lidé; Practice Guidelines as Topic; invazivní růst nádoru; Humans; průzkumy zdravotní péče; směrnice pro lékařskou praxi jako téma